Assessing Acid–Base Status in Circulatory Failure: Relationship Between Arterial and Peripheral Venous Blood Gas Measurements in Hypovolemic Shock. (May 2020) - Rudkin, Scott E.; Anderson, Craig L.; Grogan, Tristan R.; Elashoff, David A.; Treger, Richard M.
Background and Objectives: In severe circulatory failure agreement between arterial and mixed venous or central venous values is poor; venous values are more reflective of tissue acid–base imbalance. No prior study has examined the relationship between peripheral venous blood gas (VBG) values and arterial blood gas (ABG) values in hemodynamic compromise. The objective of this study was to examine the correlation between hemodynamic parameters, specifically systolic blood pressure (SBP) and the arterial–peripheral venous (A-PV) difference for all commonly used acid–base parameters (pH, Pco 2, and bicarbonate). Design, Setting, Participants, and Measurements: Data were obtained prospectively from adult patients with trauma. When an ABG was obtained for clinical purposes, a VBG was drawn as soon as possible. Patients were excluded if the ABG and VBG were drawn >10 minutes apart. Results: The correlations between A-PV pH, A-PV Pco 2, and A-PV bicarbonate and SBP were not statistically significant ( P = .55, .17, and .09, respectively). Although patients with hypotension had a lower mean arterial and peripheral venous pH and bicarbonate compared to hemodynamically stable patients, mean A-PV differences for pH and Pco 2 were not statistically different ( P = .24 and .16, respectively) between hypotensive and normotensive groups. Conclusions: In hypovolemic shock, the peripheral VBG does not demonstrate a higher CO2 concentration and lower pH compared to arterial blood. Therefore, the peripheral VBG is not a surrogate for the tissue acid–base status in hypovolemic shock, likely due to peripheral vasoconstriction and central shunting of blood to essential organs. This contrasts with the selective venous respiratory acidosis previously demonstrated in central venous and mixed venous measurements in circulatory failure, which is more reflective of acid–base imbalance at the tissue level than arterial blood. Further work needs to be done to better define the relationship between ABG and both central and peripheral VBG values in various types of shock.